Inside Cowley : trade union struggle in the 1970s : who really opened the door to the Tory onslaught? - Thornett, Alan; Loach, Ken (London : Porcupine Press, 1998)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: vakbonden; Groot-Brittannië.